LITERASI DI TENGAH PANDEMI: BAGAIMANA KEMAMPUAN LITERASI SISWA - Arif Widodo; Umar Umar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
During the pandemic, learning at elementary schools encountered many obstacles, including those related to literacy. One indicator of basic literacy skills is that having reading fluency and comprehension. During the pandemic, how are students' basic literacy skills? This study aimed to determine the profile of students' basic literacy skills during the pandemic. This study was conducted at one of the public elementary schools in Kabupaten Lombok Tengah. This study was survey research that administered a test as the instrument. The research subjects were 110 students who were selected saturated sampling technique. Data were analyzed using descriptive statistics. The survey results showed that 7% of the students were at the beginner level is 7%, while 10% of students were at the letter level. Then, 11% of the students were at the word level; 12% of them were at the paragraph level; 12% of students were at story one level as much as 12%, and 48% of students were at story level. Most of the students were not fluent in reading and could not understand the reading content. Students who were fluent in reading and able to understand the text were less than half of the population or only 48% of 110 students. These data indicated a decline in students' basic literacy skills during learning in the pandemic era.